Effects of Cutting Parameters on The Surface Roughness in CNC Turning of AISI 1050 Steel - Çaydaş, Alparslan Ulaş; Köm, Süreyya Elif; Creata, Alin George; Dragoi, Stefania-adriana; Gül, Sezer (Fırat University, 2026)
In this study, the effects of cutting parameters on surface roughness and chip types in CNC turning of AISI 1050 steel were investigated. For this purpose, cutting speed, feed rate, and depth of cut were varied to evaluate their relative influences on the measured responses. An experimental design based on the Taguchi L9 orthogonal array was employed. Four different types of chips were observed in accordance with the ISO 3685 standard. Analysis of variance (ANOVA) was conducted to determine the statistical significance of each cutting parameter in relation to surface roughness. Cutting speed was identified as the most influential factor affecting surface roughness. Feed rate was the second ranking factor. Depth of cut appeared to have no significant effect on the measured surface roughness. Additionally, the mathematical relationship between cutting parameters and surface roughness was established using regression analysis. The regression model demonstrated a high level of accuracy, with a coefficient of determination (R2) of 0.966.

Bu çalışmada, AISI 1050 çeliğinin CNC tornalanmasında kesme parametrelerinin yüzey pürüzlülüğü ve talaş tipleri üzerindeki etkileri araştırılmıştır. Kesme hızı, ilerleme miktarı ve talaş derinliği faktörlerinin çıktılar üzerindeki bağıl etkilerini belirlemek amacıyla faktör seviyeleri belirli sınırlar içerisinde değiştirilmiştir. Taguchi L9 ortogonal dizisine dayalı bir deneysel tasarım kullanılmıştır. ISO 3685 standardına göre dört farklı talaş tipi gözlemlenmiştir. Her bir kesme parametresinin yüzey pürüzlülüğüyle istatistiksel ilişkisini belirlemek için varyans analizi (ANOVA) yapılmıştır. Kesme hızı, yüzey pürüzlülüğünü etkileyen en etkili faktör olarak belirlenmiştir. İlerleme miktarı, istatistiksel olarak ikinci etkili faktör olarak tespit edilmiştir. Talaş derinliğinin ölçülen yüzey pürüzlülüğü üzerinde önemli bir etkisi olmadığı görülmüştür. Çalışmada, ayrıca regresyon analizi yöntemi kullanılarak kesme parametreleri ve yüzey pürüzlülüğü arasındaki matematiksel ilişkiler belirlenmiştir. Regresyon modeli, 0,966’ık bir doğruluk katsayısı (R2) ile yüksek bir tahmin seviyesi göstermiştir.
AISI 1050 Çelik CNC Tornalamada Kesme Parametrelerinin Yüzey Pürüzlülüğüne Etkileri
Keywords: Machining; Makine İle İşleme